Peran Guru dalam Pengembangan Kurikulum Pendidikan Islam: PERAN GURU DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM - Khoirun Nisa' (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2018)
The teacher plays a very important role both in planning and implementing the curriculum. He is a planner, implementer and curriculum developer for his class. Even if he does not trigger himself, concepts about curriculum, the teacher is a translator of the coming curriculum. The curriculum is a set of plans in the formal education process that will deliver in achieving the desired educational goals. In connection with the development of the curriculum, the role of the teacher in its development greatly influences the learning process that will be carried out both central and decentralized, both of which require the implementation and development of the teacher's role.